CORRELATION BETWEEN DURATION OF METFORMIN USE AND VITAMIN B12 DEFICIENCY IN PATIENTS WITH TYPE 2 DIABETES (The Research of Medical Science Review, 2025)
Objectives: To determine the frequency of vitamin B12 deficiency in patients with type 2 diabetes mellitus receiving long-term metformin therapy. Study Design: A Cross Sectional Study. Study Settings: Medical Unit 2, Allama Iqbal Teaching Hospital, Dera Ghazi Khan, Pakistan. Duration of Study: June’2024 to November’2024. Data Collection: A total of 222 patients aged 40–80 years with a diagnosis of T2DM and on metformin therapy for over one year were enrolled through non-probability consecutive sampling. Data on demographics, clinical history, metformin dose and duration, and comorbidities were collected. Serum vitamin B12 levels were measured; deficiency was defined as levels <125 pmol/L. Results: Of 222 cases, 54.1% were female and rest 102(45.9%) were male subjects, 60.11 ± 12.26 years was their mean age; while 28.08 ± 6.26 kg/m² BMI, 10.59 ± 5.85 years for duration of diabetes, and 10.62 ± 5.09 years as metformin usage duration. Vitamin B12 deficiency was found in 16 patients (7.2%). No statistically significant association was observed between deficiency and age, gender, smoking status, comorbidities, or metformin dose/duration (p > 0.05). Conclusion: Although the overall percentage was modest, 7.2% of diabetic patients on extended metformin therapy exhibited vitamin B12 deficiency, warranting clinical attention. While no strong associations with clinical variables were observed, routine screening for B12 levels may be helpful in preventing long-term health issues among patients in this population.